“Civilizing” the Amazon: Amerindians and the Portuguese Crown’s Struggle for Sovereignty, 1650-1777 - Duarte, Helena (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractThis article examines Portuguese colonization techniques in northern Brazil and subsequent changes during the regime of the Marquis of Pombal (1750-1777), which centred on restructuring defence, settlement, and the role of natives in the colonies. Focusing on the 1758 Indian Directorate, a collection of laws on native policy, the article examines how, despite the Enlightenment humanitarian trappings of the reform, it had a far more complex purpose than merely converting Indians into loyal subjects of the Portuguese crown. The legislation was just one part of a multi-faceted attempt to establish the crown’s sovereignty in the Amazon, which included taking power from the Jesuits, subjugating the natives, defining imperial territory, and asserting economic independence.